Climate Change in MENA : Challenges and Opportunities for the World’s Most Water Stressed Region - Sieghart, Lia Carol; Betre, Mahlette (World Bank, Washington, DC, 2018)
The Middle East and North Africa (MENA) region is no stranger to extreme temperatures. It is predicted that these extremes will worsen in the coming decades. Compounded by changing precipitation patterns, water insecurity and projected sea level rise, the region is set to experience significant challenges to its development, particularly in agriculture, livelihoods and food security. Recognizing that climate change poses an acute threat to its mission, the World Bank Group has made strong commitments to tackle the climate challenge and to work with countries to meet their climate goals. With the adoption of a Climate Change Action Plan, the Bank has laid out concrete actions which is covered in this brief, for how it intends to scale up climate action, integrate climate change across its operations, and work more closely with others, through collective action and partnerships, to implement new and innovative solutions.